Theoretical research of helium pulsating heat pipe under steady state conditions - Xu, D; Liu, H M; Li, L F; Huang, R J; Wang, W (IOP conference series. Materials Science and Engineering, 2015)
As a new-type heat pipe, pulsating heat pipe (PHP) has several outstanding features, such as great heat transport ability, strong adjustability, small size and simple construction. PHP is a complex two-phase flow system associated with many physical subjects and parameters, which utilizes the pressure and temperature changes in volume expansion and contraction during phase changes to excite the pulsation motion of liquid plugs and vapor bubbles in the capillary tube between the evaporator and the condenser. At present time, some experimental investigation of helium PHP have been done. However, theoretical research of helium PHP is rare. In this paper, the physical and mathematical models of operating mechanism for helium PHP under steady state are established based on the conservation of mass, momentum, and energy. Several important parameters are correlated and solved, including the liquid filling ratio, flow velocity, heat power, temperature, etc. Based on the results, the operational driving force and flow resistances of helium PHP are analysed, and the flow and heat transfer is further studied.